Unformatted text preview: x, y ) one computes y-3 x to determine C , that is, which line you are on. Thus the solution u ( x, y ) = h ( y-3 x ) for some as yet unknown function h ( s ). Now we use the initial condition u (0 , y ) = 1 + e 2 y . It gives us 1 + e 2 y = u (0 , y ) = h ( y ) . Consequently u ( x, y ) = 1 + e 2( y-3 x ) . [Last revised: February 28, 2012] 1...
View Full Document
This note was uploaded on 03/06/2012 for the course MATH 260 taught by Professor Staff during the Spring '12 term at UPenn.
- Spring '12